Hubungan Pengetahuan dan Dukungan Keluarga dengan Kepatuhan Pasien Mengkonsumsi Obat TB Paru - Vebry Haryati Lubis; Ismi Fatillah (STIKes IMC Bintaro, 2015)
Pulmonary TB incidence continues to increase every year, especially in Indonesia with pulmonary TB prevalence rate in 2013 is 285 per 100,000 population. In patients with pulmonary TB and a lack of knowledge of family support can affect patient adherence to treatment completely. This research aims to determine the relationship between the level of knowledge and family support with patient compliance pulmonary TB drugs in Puskesmas Pondok Aren, South Tangerang. This research uses quantitative analytic research with cross sectional method and the technique of data collection was purposive sampling with 43 respondent pulmonary TB in Puskemas Pondok Aren. The instrument of the research was a questionnaire. The analysis used is analysis of univariate and bivariate analysis with the test chi square. The result analysis showed there is relationship between the level of knowledge and family support with patient compliance pulmonary TB drugs (p=0,024; p=0,000). Implementation of nursing care to patients with pulmonary TB, namely the provision of counseling in promotive, preventive, curative, and rehabilitative as well as be the TB service team should be able to supervise or give direction to the family of patients, especially PMO to engage actively agains pulmonary TB treatment so as to minimize the transmission of pulmonary TB to others.